IMPLICATION OF ARTIFICIAL INTELLIGENCE ON NATIONAL SECURITY FOR THE NIGERIA SECURITY AGENCIES - Zakari, Musa (Journal of Terrorism Studies, 2024)
The study examines the implications of AI for national security in Nigeria in the field of military logistics for Nigerian security agencies. A documentary research design was utilized for the study. Document analysis of existing policies, reports, and case studies related to AI and national security in Nigeria was utilized. The study revealed that artificial intelligence (AI) has significant prospects for national security for Nigeria's security agencies. It was revealed that AI-powered technologies enable advanced surveillance capabilities, such as facial recognition and video analytics, which aid in identifying potential threats and monitoring security situations more effectively. The Air Force uses AI for predictive aircraft maintenance. The study revealed some challenges to the adoption and application of AI for national security in Nigeria, including a lack of awareness and understanding about the potential of AI in the security sector among policymakers and decision-makers. The study recommends that Nigeria should focus on data science and improve the capacity of coders to really automate a lot of things to be able to receive data and analyze it. The Federal Ministry of Communications Technology should be committed to supporting ICT stakeholders and strengthening a national AI ecosystem to improve the national security architecture.